2019
DOI: 10.1177/0706743719854069
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Clinical and Functional Outcomes among Patients Treated in an Early Intervention Service for Psychotic Disorders: An Observational Study

Abstract: Les diffé rences entre les sexes dans les ré sultats cliniques et fonctionnels de patients traité s dans un service d'intervention pré coce pour troubles psychotiques : une é tude par observation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 51 publications
1
18
0
1
Order By: Relevance
“…Compared with 41% of the men, 61% of the women with schizophrenia showed a period of recovery at some point during the 20-year period. Dama et al 7 suggested that some men may need more than 2 years of EIS to achieve good clinical outcomes and effectively improve their overall functioning. We suggest that patients receiving EIS beyond 3 years may continue to experience further improvements in negative symptoms and functioning, resulting in increased rates of recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared with 41% of the men, 61% of the women with schizophrenia showed a period of recovery at some point during the 20-year period. Dama et al 7 suggested that some men may need more than 2 years of EIS to achieve good clinical outcomes and effectively improve their overall functioning. We suggest that patients receiving EIS beyond 3 years may continue to experience further improvements in negative symptoms and functioning, resulting in increased rates of recovery.…”
Section: Discussionmentioning
confidence: 99%
“…A study carried out in Hong Kong with young people suffering from an FEP 6 found notable sex differences in functional outcomes, specifically in terms of higher levels of functioning in women (i.e., higher proportion of fulltime employment) within the initial 3 years of Early Intervention Services (EIS). However, in a recent observational study, Dama et al 7 , found that sex differences in outcomes among patients treated over 2 years in an EIS for psychosis in Canada could be largely affected by the disparity of other factors that exist between the two sexes (i.e., childhood and early adolescent premorbid adjustment, and age at onset of psychosis). In the Danish OPUS trial, designed for 2-, 5-, and 10-year follow-ups, it was found that almost 30% of all FEP patients improved their outcomes between 5-year and 10-year follow-ups, indicating that improvement is still possible late in illness course 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Robust sex disparities are recognized in schizophrenia incidence, age of onset, risk factors, symptomatology, and disease course [ 1 ▪▪ ]. Men experience more severe negative and cognitive symptoms and perform worse on social functioning, whereas affective symptoms, self-harm, and suicide attempts are more frequent among women [ 1 ▪▪ , 2 , 3 ]. This different presentation can cause diagnostic delay in women [ 1 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…Data on the duration of untreated psychosis in men and women are contradictory. In some studies, this duration in men has been shown to be significantly higher (Cohen et al, 2000; Dama et al, 2019; Pu et al, 2019), while it does not differ in others (Choi et al, 2009; Hui et al, 2014; Segarra et al, 2012). The age of the first hospitalization and the duration of untreated psychosis depends not only on the age of onset but also additionally on an environmental factor, such as the diagnosis age, social support of the patient, socio‐cultural and socio‐economic factors, knowledge about the disease, differences in health systems and state support (Häfner, 2019; Hui et al, 2014).…”
Section: Discussionmentioning
confidence: 95%
“…A study by Pang, concentrating on symptoms remission after 3 months, 6 months and 1 year showed that women have a better course of the disease (Pang et al, 2016). Dama et al (2019) showed that women were more likely to achieve remission of symptoms than men after 2 years of treatment. Our study did not show explicit sex differences, only for the G subscale in PANSS and DSM‐5, where the difference in scores before and after treatment differed by 3 and 1, respectively.…”
Section: Discussionmentioning
confidence: 99%